Cat's eye - Atwood, Margaret, 1939- (London : Virago, 2014)
Painter Elaine Risley, pushing fifty, returns to Toronto for a retrospective of her celebrated work. While there she takes time to confront her past.
Adult.
Adult
Keywords: Women painters -- Ontario -- Toronto -- Fiction; Women painters -- Fiction; Toronto (Ont.) -- Fiction; Domestic fiction